2004
DOI: 10.1111/j.1439-0310.2004.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Approach Strategy by which Male Mediterranean Tarantulas Adjust to the Cannibalistic Behaviour of Females

Abstract: In sexually cannibalistic species, selection is thought to have favoured the evolution of male approaching behaviour that reduces the probability that the female will kill the male. However, investigations of behaviours that could reduce the probability of sexual cannibalism are few. We examine the hypothesis that male wolf spiders, Lycosa tarantula (L.) (Araneae, Lycosidae), decides to approach females in periods when they are less dangerous. Males of this species approach females for mating during the daytim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…This behaviour has also been observed in many other cannibalistic spider and mantid species (Robinson and Robinson 1979;Prenter et al 1994;Moya-Larano et al 2004;Fromhage and Schneider 2005;Gemeno and Claramunt 2006). For example, male Mantis religiosa move towards feeding or grooming females more rapidly than they approach inactive females (Gemeno and Claramunt 2006), and male orb-web spiders Nephila plumipes typically initiate courtship and mating after the female has captured a prey item (Elgar and Fahey 1996).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This behaviour has also been observed in many other cannibalistic spider and mantid species (Robinson and Robinson 1979;Prenter et al 1994;Moya-Larano et al 2004;Fromhage and Schneider 2005;Gemeno and Claramunt 2006). For example, male Mantis religiosa move towards feeding or grooming females more rapidly than they approach inactive females (Gemeno and Claramunt 2006), and male orb-web spiders Nephila plumipes typically initiate courtship and mating after the female has captured a prey item (Elgar and Fahey 1996).…”
Section: Discussionmentioning
confidence: 60%
“…In fact, a wide variety of such traits have been proposed, including elaborate courtship displays (Polis and Farley 1979;Liske and Davis 1987;Elgar and Nash 1988;Lelito and Brown 2006), cautious approach behaviours (Roeder 1935;Liske and Davis 1987;Maxwell 1999b;Lelito and Brown 2006), and opportunistic mating whilst a female is feeding (Prenter et al 1994;Elgar and Fahey 1996;MoyaLarano et al 2004;Fromhage and Schneider 2005;Gemeno and Claramunt 2006). However, there is very little direct evidence that these behaviours actually reduce the risk of sexual cannibalism for males, and the evidence that does exist comes mainly from studies of spiders (Moya-Larano et al 2004;Fromhage and Schneider 2005). For example, Fromhage and Schneider (2005) found that opportunistic mating with feeding females greatly reduced the risk of cannibalism and injury for male Nephila fenestrata.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in the cases when females attacked one of the courting males – usually the one that approached them prematurely, the two unassaulted males both immediately began to mount the female, apparently taking advantage of the female being occupied with handling her prey (see also Birkhead et al. 1988; Moya‐Laraño et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Risk-sensitive behavioral strategies are also expected. For example, in cannibalistic Mediterranean tarantulas, males approach and court females outside the hunting periods (Moya-Larano et al 2004). In many species, males adopt opportunistic strategies and copulate while the female is occupied with feeding or while she is molting to maturity (Robinson and Robinson 1980;Fromhage and Schneider 2005c).…”
Section: Responses To the Threat Of Sexual Cannibalismmentioning
confidence: 99%